Strategi Tindakan Sosial Nazir Yayasan Pendidikan Islam Nurul Amal Parang untuk Pengembangan Wakaf Produktif - Bayu Setiyawan; Abid Rohmanu; Ahmad Junaidi (Institut Agama Islam Negeri Ponorogo, 2024)
This research was motivated by the researcher's interest in seeing the success of Nazir in developing productive waqf at the Nurul Amal Parang Islamic Education Foundation. Because the majority of use of waqf land assets in Parang District tends to be towards conventional or unproductive waqf. So far, only YPI Nurul Amal has been able to manage its waqf assets into productive waqf. When founding YPI Nurul Amal Parang, Nazir had his own motives and goals and correlated with Max Weber's theory of social action. This research uses case study field research with a qualitative approach. Data collection techniques through interviews, observation and documentation. The aim of this research is to describe the implementation of productive waqf at the Nurul Amal Parang Islamic Education Foundation. Apart from that, this research aims to find out the background of the Nurul Amal Parang Islamic Education Foundation in managing its waqf assets productively. This research is also aimed at exploring information about the implications of the existence of productive waqf at YPI Nurul Amal Parang. The findings obtained by researchers regarding the social actions of the Nurul Amal Parang Islamic Education Foundation to develop productive waqf The aim of productive waqf management at YPI Nurul Amal Parang is for the benefit of facilities and infrastructure in the field of educational institutions, and The implications of productive waqf with the existence of YPI Nurul Amal Parang have a positive impact on the wider community in the fields of education, religion and economics.